2017
DOI: 10.1108/imefm-11-2015-0137
|View full text |Cite
|
Sign up to set email alerts
|

Does Islamic banking really strengthen financial stability? Empirical evidence from Pakistan

Abstract: Purpose This paper aims to empirically assess the contribution of Islamic banks toward the financial stability of Pakistan. For this, the authors investigate the relative financial strength of Islamic banks and their contribution toward the financial stability. They also examine the relationship between the competitive conduct of banks and banking system stability. Design/methodology/approach The authors use quarterly data of ten conventional banks, four full-fledged Islamic banks and six standalone Islamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
3
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 24 publications
7
53
3
5
Order By: Relevance
“…The following is a general overview of financing data and NPF of sharia banking Indonesia 2011-2016: After the regression test with 5% significance using eviews, it showed that the financing of MSMEs as a proxy for financial inclusion has no effect on the financial stability of Sharia banking, but contrastly deposits has positive effect. This result support the finding of Rashid et al (2017) that Sharia banks income does not solely depend on lending and rely on different source of income that positively contribute to improving the financial stability of those Sharia banks. Hypothesis testing that has been done shows financial inclusion proxies by deposits have positive effect on Sharia banking stability of while proxy financing of MSMEs has no effect.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The following is a general overview of financing data and NPF of sharia banking Indonesia 2011-2016: After the regression test with 5% significance using eviews, it showed that the financing of MSMEs as a proxy for financial inclusion has no effect on the financial stability of Sharia banking, but contrastly deposits has positive effect. This result support the finding of Rashid et al (2017) that Sharia banks income does not solely depend on lending and rely on different source of income that positively contribute to improving the financial stability of those Sharia banks. Hypothesis testing that has been done shows financial inclusion proxies by deposits have positive effect on Sharia banking stability of while proxy financing of MSMEs has no effect.…”
Section: Resultssupporting
confidence: 89%
“…The role of Islamic or Sharia banking in promoting financial system stability is an important issue. There are some evidence that Islamic or Sharia banks contribute positively to the financial stability of banking sector and in turn, to the economy (Rashid et al, 2017;Borkhis&Nabi, 2013). However, the said impact has not been well researched in case of Sharia banking in Indonesia.…”
Section: The Role Of Financial Inclusion Toward Financial Stabilitymentioning
confidence: 99%
“…Rashid and Rehman (2016) measuring and decomposing the total factor productivity and efficiency of banks in Pakistan indicated that the total factor productivity of conventional banks was higher than that of Islamic banks. Rashid, Yousaf, and Khaleequzzaman (2017) examined the role of Islamic banks in the financial stability of financial sector of Pakistan. They found that compared to conventional banks, Islamic banks were better and more effectively contributing in the stability of financial sector.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Hasil pengujian korelasi dengan meniadakan variabel kontrol didapatkan bahwa tingkat stabilitas berkorelasi positif dan signifikan dengan financing to deposit ratio (FDR) dengan nilai koefisien 0,268. Semakin tinggi nilai z-score, maka semakin stabil keuangan bank dan jauh dari kegagalan finansial dan akan meningkatkan rasio pembiayaan, hasil ini mirip dengan hasil studi yang dilakukan oleh Rashid et al, (2017) yang menyatakan bahwa ada hubungan antara loan (kredit) dengan stabilitas. Namun stabilitas tidak memiliki hubungan yang signifikan dengan akad pembiayaan murabahah.…”
Section: Gambar 1 Rata-rata Inflasi Nasional Per Tahununclassified